Marketing Strategy Analysis with SWOT and QSPM Methods at PT Wedhatama Sukses Makmur, Singaraja, Bali - Sitorus, Helen Wahyuni; Aviantara, I Gusti Ngurah Apriadi; Pudja, Ida Ayu Rina Pratiwi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
PT Wedhatama Sukses Makmur is an organic fertilizer company based on animal manure (guano). This company has not used the SWOT and QSPM methods in its marketing strategy. It can be seen in bookkeeping problems and ineffective marketing performance, resulting in sales targets not being achieved. This study aims to determine alternative strategies formulated through the factors that are the determinants in marketing the products produced by the company using the SWOT and QSPM methods. The results showed that PT Wedhatama Sukses Makmur had 14 internal factors (nine strength factors and five weakness factors) and 11 external factors (seven opportunity factors and four threat factors). The total IFE matrix is 3,06, the EFE matrix is 3,51, and the IE matrix is the company's position in quadrant I (Growth and Build). The results of the SWOT analysis show that there are eight alternative strategies. The priority strategy from the QSPM analysis is to improve the management system, improve the company's technical capabilities, and increase the number of human resources (especially in the marketing field) to achieve sales targets with a total TAS score of 7,78.